Dialogues across Disciplines: Preparing English-as-a-Second-Language Teachers for Interdisciplinary Collaboration - Margo DelliCarpini (Arizona State University, 2015)
This study examines interdisciplinary collaboration between mainstream-English and English-as-a-second-language (ESL) in-service and pre-service teachers enrolled in graduate methods courses in their respective fields. During the semester, TESOL and secondary English Education teacher candidates collaborated to develop young adult literature based thematic units that supported the curricular needs of the secondary English education curriculum in the ESL classroom and the provided for the linguistic, second-language-literacy, and cultural needs of English language learners (ELLs) in the mainstream English classroom through interdisciplinary teacher collaboration.